Bloodbath - Pansegrouw, Nicholas Arthur (Rhodes University, 2026)
This thesis examines the persistence of violence in post-apartheid South Africa through three historical periods: the Sharpeville Massacre and its aftermath, 1980s anti-apartheid resistance and state response, and post-1994 violence along with the shortcomings of the Truth and Reconciliation Commission (TRC). Marked by interconnected socio-political dynamics, each of these periods has helped shape South Africa’s modern-day ‘culture of violence’. The 1960 Sharpeville Massacre was a pivotal moment in South African history. Domestically, it intensified repression and entrenched a system of institutionalised violence that shaped the nation’s socio-political framework. Internationally, it sparked widespread condemnation of apartheid. By the 1980s, anti-apartheid resistance, termed ‘Total Onslaught’ by the state, faced the government's ‘Total Strategy’, setting off a cycle of violence that left physical destruction and psychological distress on a mass scale. Post-1994, South Africa's democratic transition aimed at nation-building via healing and reconciliation, the TRC mandated with addressing apartheid-era trauma. However, the TRC's limited scope and lack of accountability left unresolved grievances, which in turn have fueled ongoing violence rooted in fractured social structures and omnipresent inequality. These analyses highlight the challenges modern-day South Africa faces, with past injustices and socio-political inconsistencies continuing to shape the country’s violent present. By addressing systemically troublesome issues, fragile social frameworks, and omnipresent inequality, opportunities exist to reduce violence and bring about meaningful societal change within the country.
comparative analysis of three historical periods (the Sharpeville massacre and its aftermath, anti-apartheid resistance and state response, post-1994 : contemporary violence and the TRC’s shortcomings) exploring the persistence of violence in post-apartheid South Africa
Keywords: Uncatalogued